Telemedicine and visual impairment – opportunities, threats, challenges - Binder-Olibrowska, Katarzyna (Virtualizing the lives of people with disabilities, 2021)
Telemedicine has been evolving for years, and the prevalence of its use spurred by the SARS-CoV-2 pandemic has made it difficult to imagine healthcare without it in the future. As with other healthcare activities, there is a need to control the quality of telemedicine interventions. One of the determinants of this quality is the fit between the services and the needs of the recipients. For years, attention has been drawn to the inequalities in access to health care experienced by people with disabilities. Hence, the question is whether telemedicine is an opportunity to achieve equality or is it another threat for this group of people? What challenges are associated with the use of technology-based health care services? This study is an attempt to answer these questions in relation to people with visual dysfunctions.